2012
DOI: 10.1002/emmm.201100211
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule Inauhzin inhibits SIRT1 activity and suppresses tumour growth through activation of p53

Abstract: Although ∼50% of all types of human cancers harbour wild-type TP53, this p53 tumour suppressor is often deactivated through a concerted action by its abnormally elevated suppressors, MDM2, MDMX or SIRT1. Here, we report a novel small molecule Inauhzin (INZ) that effectively reactivates p53 by inhibiting SIRT1 activity, promotes p53-dependent apoptosis of human cancer cells without causing apparently genotoxic stress. Moreover, INZ stabilizes p53 by increasing p53 acetylation and preventing MDM2-mediated ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
120
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 82 publications
9
120
0
Order By: Relevance
“…Tumor volume (mm 3 ) was calculated as (length  width 2 )/2. 58 Mice were killed 40 days after treatment, and tumors were excised and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor volume (mm 3 ) was calculated as (length  width 2 )/2. 58 Mice were killed 40 days after treatment, and tumors were excised and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18]22 However, whether INZ could function to suppress the expression of c-Myc and inhibit lymphoma cell growth remains unknown. To this end, we treated human lymphoma Boston cells with INZ(c), an INZ analog with better potency.…”
Section: Inz(c) Suppresses C-myc Expression In a P53-independent Mannermentioning
confidence: 99%
“…We previously showed that INZ does not introduce noticeable DNA damage 15 and could sensitize p53-dependent cytotoxicity and tumor suppression of chemotherapeutic agents, such as doxorubicin (Dox). 17 Therefore, we next checked whether INZ(c) could cooperatively target c-Myc expression with doxorubicin, as doxorubicin had been shown to suppress c-Myc expression.…”
Section: Inz(c) Cooperatively Suppresses C-myc Expression With Doxorumentioning
confidence: 99%
See 2 more Smart Citations